HTX-019: polysorbate 80- and synthetic surfactant-free neurokinin 1 receptor antagonist for chemotherapy-induced nausea and vomiting prophylaxis. (11th October 2018) - Navari, Rudolph M
Chemotherapy-induced nausea and vomiting (CINV) may occur during the acute (0–24 h) or delayed (25–120 h) phase following chemotherapy administration. The addition of a neurokinin 1 receptor antagonist to antiemetic regimens containing a 5-hydroxytryptamine type 3 receptor antagonist and dexamethasone has resulted in improved CINV prophylaxis. Due to numerous adverse events and hypersensitivity reactions associated with fosaprepitant, a commonly used neurokinin 1 receptor antagonist, there remains an unmet need for better-tolerated formulations. HTX-019, the US FDA-approved polysorbate 80- and synthetic surfactant-free aprepitant injectable emulsion, is bioequivalent to and better tolerated (fewer treatment-emergent adverse events) than fosaprepitant. HTX-019 represents a valuable alternative to fosaprepitant for CINV prophylaxis.